Traditional Chinese Medicine in Depression Treatment: From Molecules to Systems - Li, Chan; Huang, Junying; Cheng, Yung-Chi; Zhang, Yuan-Wei (Frontiers in Pharmacology, 2020)
Depression is a multigenetic or multifactorial syndrome. The central neuron system (CNS)-orientated, single target, and conventional antidepressants are insufficient and far from ideal. Traditional Chinese Medicine (TCM) has historically been used to treat depression up till today, particularly in Asia. Its holistic, multi-drug, multi-target nature fits well with the therapeutic idea of systems medicine in depression treatment. Over the past two decades, although efforts have been made to understand TCM herbal antidepressants at the molecular level, many fundamental questions regarding to their mechanisms of action remain to be addressed at the systems level in order to better understand the complicated herbal formulations in depression treatment. In this Mini Review, we review and discuss the mechanisms of action of herbal antidepressants and their acting targets in the pathological systems in the brain, such as monoamine neurotransmissions, hypothalamic–pituitary–adrenal (HPA) axis, neurotropic factor BDNF cascade, and glutamate transmission. Some herbal molecules, constituents, and formulas are highlighted as examples to be discussed their mechanisms of action and future directions for comprehensive researches at the systems level. Furthermore, we discuss pharmacological approaches to integration the mechanism of action from the molecular level into the systems level for understanding of systems pharmacology of TCM formulations. Integration of the studies at the molecular level into the systems level not only represents a trend in TCM study but also promotes our understanding of the systemwide mechanism of action of herbal antidepressant formulations.